"Surface, " "satellite" or "simulation": Mapping intra‐urban microclimate variability in a desert city. (19th November 2019) - Zhou, Bin; Kaplan, Shai; Peeters, Aviva; Kloog, Itai; Erell, Evyatar
Abstract: Mapping spatial and temporal variability of urban microclimate is pivotal for an accurate estimation of the ever‐increasing exposure of urbanized humanity to global warming. This particularly concerns cities in arid/semi‐arid regions which cover two fifths of the global land area and are home to more than one third of the world's population. Focusing on the desert city of Be'er Sheva Israel, we investigate the spatial and temporal patterns of urban–rural and intra‐urban temperature variability by means of satellite observation, vehicular traverse measurement, and computer simulation. Our study reveals a well‐developed nocturnal canopy layer urban heat island in Be'er Sheva, particularly in the winter, but a weak diurnal cool island in the mid‐morning. Near surface air temperature exhibits weak urban–rural and intra‐urban differences during the daytime (<1°C), despite pronounced urban surface cool islands observed in satellite images. This phenomenon, also recorded in some other desert cities, is explained by the rapid increase in surface skin temperature of exposed desert soils (in the absence of vegetation or moisture) after sunrise, while urban surfaces are heated more slowly. The study highlights differences among the three methods used for describing urban temperature variability, each of which may have different applications in fields such as urban planning, climate change mitigation, and epidemiological research. Abstract : Focusing on the desert city of Be'er Sheva Israel, this study investigates the spatio‐temporal patterns of urban–rural and intra‐urban temperature variability by means of vehicular traverse measurement (a), satellite observation (b), and computer simulation (c). We reveal a well‐developed nocturnal canopy layer urban heat island, particularly in the winter, but a weak diurnal cool island in the mid‐morning. Near surface air temperature exhibits weak urban–rural and intra‐urban differences during the daytime (<1°C), despite pronounced urban surface cool islands observed from satellites.